Practicing Home in the Foreign: 'The multiple homing practices of artisan journeymen on the tramp' - Dorte Jagetic Andersen; René Ejbye Pedersen (Nordic Journal of Migration Research, 2018)
Research in migrant practices has recognised that home crystallises into multiple forms subject to constant re-enactment when viewed from the perspective of mobile populations such as nomads and refugees. In this article, we illustrate how artisan journeymen who went on the tramp around the turn of the 20th century performed home in multiple ways when on the road and at arrival in new locations. Using a historical example, we oppose the suggestion, which is common in contemporary migration and transnational studies that recent years have witnessed a paradigmatic new way of enacting belonging. Ultimately, the argument is that instead of idealising certain notions of the traveller, or ways of practicing home, we need to keep an eye to the real-life tensions of homing and the multiplicity through which it expresses; we need to understand homing as the performance of “belonging trouble.”